Corporate Governance, Financial Performance and Macroeconomics: The Impact on Bank Profitability Information - Priharta, Andry; Gani, Nur Asni; Munawaroh, Azizatul; Ananto, Tri (Universitas Swadaya Gunung Jati, 2023)
Banks are institutions with stringent regulations related to corporate governance implementation and the demand for high financial performance. Macroeconomic conditions significantly affect the financial performance, including profitability, of banks. The study focused on Indonesia's four state-owned banks, Bank Tabungan Negara (BBTN), Bank Negara Indonesia (BBNI), Bank Rakyat Indonesia (BBRI), and Bank Mandiri (BMRI). The research sample or saturated sample was the entire population. The 10-year observation period ran from 2011 to 2020. The panel data regression model with a common effect was used to evaluate the data. The data showed that CGPI and LDR had no discernible impact on profitability. While NPL and FOREX had a large negative impact on profitability as evaluated by ROA, CAR, NIM, SIZE, and BIRATE had a significant positive impact. All independent factors simultaneously have a major impact on profitability. All independent factors were able to explain their impact on profitability to a degree of 94.39%, according to adjusted R-squared, while other variables outside the model were responsible for the remaining effects.